Immuno-genomic landscape of osteosarcoma - Chia-Chin Wu (Nature Portfolio, 2020)
The efficacy of immune checkpoint inhibitors (ICI) in osteosarcoma has been limited. Here, the authors investigate the immunogenomic landscape of osteosarcoma, and integrated analyses highlight features related to a suppressed immune microenvironment.